Longitudinal Association Between Ideal Cardiovascular Health Status and Muscular Fitness in Adolescents: The Labmed Physical Activity Study - Garcia-Hermoso, A (Elsevier B.V., 2018)
Background and aims: Muscular fitness is an emerging predictor for cardiovascular disease mortality. The ideal cardiovascular health metrics has been inversely related to a subsequent cardiometabolic health in adulthood. However, evidence regarding muscular fitness and ideal cardiovascular health in adolescents is scarce. This study aimed to examine the longitudinal association between ideal cardiovascular health index and muscular fitness. Methods and results: This study cohort consisted of 331 adolescents (183 girls) from the LabMed Physical Activity Study who were followed from 2011 to 2013. Ideal cardiovascular health, as defined by the American Heart Association, was determined as meeting ideal health factors (total cholesterol, blood pressure, and glucose) and behaviors (smoking status, body mass index, physical activity, and diet). Handgrip strength and standing long jump tests assessed muscular fitness and were transformed into standardized values according to age and sex. ANCOVA showed a significant association between the accumulation of ideal cardiovascular health metrics at baseline and muscular fitness indices at follow-up (F (4, 322) = 2.280, p = 0.04). In addition, the higher the number of ideal cardiovascular health metrics accumulated, the higher the likelihood of having a high muscular fitness over a two-year period (p for trend = 0.01), after adjustments for age, sex, pubertal stage and socioeconomic status and muscular fitness at baseline. Conclusion: The ideal cardiovascular health status during adolescence was associated with high muscular fitness levels over a two-year period. © 2018 The Italian Society of Diabetology, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition, and the Department of Clinical Medicine and Surgery, Federico II University